Optimalisasi Kinerja PT. BPR X Kebumen - Mai Satriyani; Hanung Eka Atmaja; Budi Rahardjo (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2022)
Performance is something that is important for the continuity of the company. Companies are required to be able to identify, manage, and improve business processes. This study aims to assess the performance of PT. BPR X Kebumen with a balanced scorecard approach that is assessed from four perspectives. This study uses a balanced scorecard and analytical hierarcy process for measurement and looking for performance optimization solutions at PT. BPR X Kebumen. Data collection carried out at PT. BPR X Kebumen with in-depth interviews with experts, financial statement data, and observations. The results showed that the financial perspective had the highest weighting results with a value of 0.359. The internal business process perspective has the second highest value with a value of 0.264. The customer perspective ranks third with a value of 0.244, and the last is the growth and learning perspective with a weighting result of 0.133. The results of this study can be used by PT. BPR X Kebumen as a performance optimization strategy at PT. BPR X Kebumen.